Savonius Hydrokinetic Turbine : A Bibliometric Analysis - Muhyiddin, Mohammed; Shamsul, Sarip; Sa'ardin, Abdul Aziz; Wan Azani, Mustafa; Ahmed Ali, Ajmi (SEMARAK ILMU SDN BHD, 2025)
The Savonius Hydrokinetic Turbine (SHT) exhibits promise as a viable option for a power extraction apparatus capable of harnessing energy from diverse water flow situations, such as tidal, river, wave, and open channel settings. The SHT is considered a simple and straightforward design, including convenient manufacturing and installation processes. This investigation’s primary purpose is to ascertain the current trends as well as upcoming areas of research pertaining to the SHT, thereby enhancing its potential for environmental sustainability. Through bibliometric studies, this article discusses global research trends in SHT based on publication output and co-occurrence of author keywords. The data were examined using VOSviewer. Metadata was obtained from Scopus, which consisted of 76 articles published between 2019 and September 2023. The VOSviewer software reviewed four clusters. The most frequently used keywords were 'hydrokinetic turbines', 'turbine', 'power coefficients', 'Savonius turbine', 'turbomachine blade', and 'Computational Fluid Dynamics (CFD)'. The outcomes of the research initiated by SHT has provided significant findings, emphasising the significance of comprehending blade profile design for the best use of this novel energy solution.